Case presentation of a 12 year old with pulmonary alveolar proteinosis. (24th May 2012) - Austin, S; Connett, G
Abstract : Aims: To highlight a rare respiratory condition, its investigation and management. Methods: A 12 year old girl referred by GP to her local DGH with a history of worsening exertional and nocturnal dyspnoea, and weight loss subsequent to a flu like illness one year previously. Past medical history was unremarkable. Her exercise tolerance was severely restricted due to cough and shortness of breath. She had shown no response to either bronchodilators or inhaled steroids. She had been treated with 3 courses of oral antibiotics for presumed chest infections without improvement. Results: She was dyspnoeic at rest, hypoxic in room air (85%), which improved to 93% in 1 litre of oxygen. She was thin but not clubbed. She had marked pectus excavatum. She had markedly reduced air entry and coarse crackles bilaterally. Her chest X-ray showed widespread interstitial shadowing. She had normal routine bloods, blood gas, and ECG. Her FEV1 was 30% predicted with a restrictive flow-volume loop. Her differential diagnoses included pneumocystis pneumonia, drug reaction, interstitial lung disease, and alveolar proteinosis. She was referred to her regional respiratory centre. Further investigations of note were: ▶ Pneumocyctis PCR: Negative ▶ Bronchoscopy: Normal airway anatomy. Creamy BAL fluid. ▶ Immune function: Normal ▶ CT Chest: widespread alveolar and interstitial change, with 'crazy paving' ▶ Echo: Normal ▶ Quantiferon & AFB staining: Negative ▶ BAL showed abnormal cytology, with amorphous proteinaceous debris. Strongly PAS stain positive, diagnostic for Pulmonary Alveolar Proteinosis (PAP). She also grew haemophilus resistant to amoxicillin, commenced on co-amoxiclav. Conclusion: PAP can present in the neonatal period, due to surfactant protein B deficiency, and is usually fatal. Later onset disease can be related to disturbance of granulocyte-macrophage colony stimulating factor (GM-CSF), and is diagnosed on BAL without the need for lung biopsy. CT appearances are suggestive. She was referred to the Royal Brompton for bilateral whole lung lavage. Ongoing care issues include correction of hypoxaemia, improving nutritional status, repeat lavage treatment and consideration of inhaled GMCSF. This condition has a variable course. Some patients will have spontaneous remission, some will have their disease controlled with multiple lavage treatments and some have disease with progression to respiratory failure.